Free Radical Scavenging Activity of Salvadora persica Linn. - ARORA, SAAHIL; KAUSHIK, D. (Asian Journal of Chemistry, 2010)
This study comprises of in vitro antioxidant activity on hydro alcoholic (SPHA) and aqueous (SPW) extracts from shade dried roots of Salvadora persica L. by various models. Both SPHA and SPW extracts showed significantly high scavenging ability on 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical (87.60 and 72.29 % at 400 μg/mL), 2,2-azino bis(3-ethyl benzothiazoline-6-sulphonic acid (ABTS) radical (87.50 and 78.45 % at 500 μg/mL), superoxide nitroblue-tetrazoliun (NBT) radical (54.39 and 42.25 % at 600 μg/mL) and reduction of ferric ion solution (73.10 and 64.90 % at 500 μg/mL). Result indicates the powerful electron donating and radical scavenging activity of S. persica L. Hence both the extracts can be considered as effective chain breaking in vivo antioxidants.